A highly specific and ultrasensitive probe for the imaging of inflammation-induced endogenous hypochlorous acid. Issue 11 (1st May 2019) - Song, Xinjian; Hu, Wei; Wang, Donghua; Mao, Zhiqiang; Liu, Zhihong
Abstract : A two-photon fluorescent probe with high sensitivity and selectivity was constructed and applied to visualize endogenous HOCl in lipopolysaccharide-induced inflammation. Abstract : A turn-on two-photon fluorescent probeHCA-Green for hypochlorous acid (HOCl) was synthesized using 4-methylamino-1, 8-naphthalimide (MNA ) as a two-photon fluorophore and p -hydroxyaniline as a leaving-recognition domain. Both the probe and the fluorophore were investigated under one- and two-photon excitation modes. The fluorescence intensity of the probe was enhanced by ∼229-fold and ∼193-fold under one-photon and two-photon excitation, respectively, after reacting with HOCl. A maximal two-photon action cross-section of 50 GM was obtained under excitation at 810 nm. The probe exhibited high sensitivity with a detection limit of 42.3 nM, as well as high selectivity, low cytotoxicity, and good photostability. Two-photon microscopy (TPM) was conducted to visualize HOCl levels in living cells and tissues. The production of endogenous HOCl induced by lipopolysaccharide-mediated inflammation was successfully monitored with this probe.